(x+3)(x-4)=o

Simple and best practice solution for (x+3)(x-4)=o equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)(x-4)=o equation:


Simplifying
(x + 3)(x + -4) = o

Reorder the terms:
(3 + x)(x + -4) = o

Reorder the terms:
(3 + x)(-4 + x) = o

Multiply (3 + x) * (-4 + x)
(3(-4 + x) + x(-4 + x)) = o
((-4 * 3 + x * 3) + x(-4 + x)) = o
((-12 + 3x) + x(-4 + x)) = o
(-12 + 3x + (-4 * x + x * x)) = o
(-12 + 3x + (-4x + x2)) = o

Combine like terms: 3x + -4x = -1x
(-12 + -1x + x2) = o

Solving
-12 + -1x + x2 = o

Solving for variable 'x'.

Reorder the terms:
-12 + -1o + -1x + x2 = o + -1o

Combine like terms: o + -1o = 0
-12 + -1o + -1x + x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 30x+50y=240 | | 29=b/4+15 | | 5b+1/2b+2b+1/3b | | (7/8)x+1=(5/8)x | | -17+t/5=3 | | 3x/2-4=21 | | x^3-3x^2-8x+12=0 | | 10+11x=40+x | | 15n^2+17n-4=0 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5(2y+1)=3(4-5y) | | 9+-8x=40-15x | | 3(2x-5)=-1 | | 8x-29=3x+1 | | 3x-2=10-3x | | 5+3(-2x+2)=6-4(x+1) | | 9-8x=34x+23 | | 15x-7=9+7x | | 8(9+b)-4b= | | 3r+17-2r+6= | | v^2-16v-20=-5 | | -10=5g | | n^2+16-80=0 | | 10=50e^2(x-1) | | r^2-2=34 | | 4x+24=14-66 | | 2(x+5)=3(10-x) | | X^2+10=4 | | 10x+-6=8x+4 |

Equations solver categories